The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/13607863.2013.837147
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership may attenuate loneliness among older adult primary care patients who live alone

Abstract: Objectives Older adults who report feelings of loneliness are at increased risk for a range of negative physical and mental health outcomes, including early mortality. Identifying potential sources of social connectedness, such as pet ownership, could add to the understanding of how to promote health and well-being in older adults. The aim of this study is to describe the association of pet ownership and loneliness. Methods The current study utilizes cross-sectional survey data from a sample (N = 830) of old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 35 publications
(38 reference statements)
2
103
0
6
Order By: Relevance
“…Pets can serve as a buffer against feelings of loneliness and may compensate for low (human) social connectedness (Barker and Wolen 2008;Garrity et al 1989). For example, a recent study of older adults who presented to their primary care physician found that those owning a pet were 36 % less likely to report loneliness than older adults without pets (Stanley et al 2014). Due in part to the results of these studies, the unique relationship older people share with their dogs as emotional companions has gained growing attention (Scheibeck et al 2011).…”
Section: Loneliness and Isolationmentioning
confidence: 95%
See 2 more Smart Citations
“…Pets can serve as a buffer against feelings of loneliness and may compensate for low (human) social connectedness (Barker and Wolen 2008;Garrity et al 1989). For example, a recent study of older adults who presented to their primary care physician found that those owning a pet were 36 % less likely to report loneliness than older adults without pets (Stanley et al 2014). Due in part to the results of these studies, the unique relationship older people share with their dogs as emotional companions has gained growing attention (Scheibeck et al 2011).…”
Section: Loneliness and Isolationmentioning
confidence: 95%
“…When their job ends, they tend to have less involvement with others, which can lead to a downward spiral of reduced social contact. Social support has been associated with positive physical benefits, including reduced risk of developing heart disease, getting cancer or AIDS/HIV, as well as psychological benefits such as reduced risk of stress, depression, anxiety (Stanley et al 2014;Cacioppo et al 2002;Barth et al 2010;Pauley and Hesse 2009;Nurullah 2012). It has been suggested that social support may reduce perceptions of stressful events, and even protect people against anxiety-related illness and enhance recovery from such serious health risks such as strokes, heart attacks, and cancer (McNicholas and Collis 2004).…”
Section: Loneliness and Isolationmentioning
confidence: 97%
See 1 more Smart Citation
“…Raina et al (1999) concluded that companion animals helped maintain or enhance the physical health of older people and could also positively affect their psychological well-being. Since the study by Raina et al was published 15 years ago, it is interesting to find that also a more recent study of 830 older adults, comparing pet owners with non-pet owners, confirmed that pet ownership may confer benefits for well-being, including attenuating feelings of loneliness (Stanley et al, 2014). A random survey of 339 adults in Australia (17% aged ≥60 years) showed that pet ownership provides opportunities for interactions between neighbours (Wood et al, 2005), which was also found in our study.…”
Section: Perceiving Animals As Family Membersmentioning
confidence: 98%
“…It is well known that animals have a similar effect on people, and as a matter of fact may encompass the three aspects of a confidant as defined by Camozzato's group. Pet ownership has recently been shown to attenuate loneliness among elderlies living alone [7]. Other studies have shown it to reduce blood pressure and maintain a normal heart rate [8].…”
mentioning
confidence: 99%